Dual targeting of G9a and DNMTs induces antitumor effects in multiple myeloma - Nylund, Patrick; Garrido-Zabala, Berta; Tziola, Stefania Iliana; Mohajershojai, Tabassom; Berglund, Hanna; Muylaert, Catharina; Van Hemelrijck, Lien Ann; Párraga, Alba Atienza; Vasquez, Louella; Jacob, Jim; Bergquist, Eric; Martín-Subero, José Ignacio; et al. (Blood Advances, 2025)
Multiple myeloma (MM) is a hematological disease of the plasma cell that remains clinically challenging despite the development of novel therapies. Epigenetic alterations have been demonstrated to contribute to MM pathogenesis, yet comprehensive studies into the links between different epigenetic regulatory systems in myeloma progression and drug resistance, though clinically relevant, are largely lacking. G9a and the DNA methyltransferases (DNMTs) are epigenetic modifiers that exhibit increased activity in MM, correlating with poor prognosis. To investigate the partnership between G9a and DNMTs, we used a combinatorial treatment approach involving small-molecule inhibitors. In-depth molecular analysis of the histone H3 lysine dimethylation distribution, the DNA methylome and the transcriptome of MM revealed a silencing mechanism involving G9a and DNMTs that represses key tumor suppressor genes. Moreover, dual inhibition of G9a and DNMTs reduced cell viability in primary MM cells and induced apoptosis in MM cell lines. This was accompanied by increased expression of apoptosis-related genes and decreased protein levels of the MM-associated oncoproteins IRF4, XBP1, and MYC. To assess the translational relevance of our in vitro findings, we evaluated the combination therapy in an in vivo preclinical xenograft MM model. Specifically, we demonstrate that the G9a inhibitor A366 synergizes with the DNMTs inhibitor decitabine to promote a robust tumor regression in vivo. Together, these data provide new insights into the cooperative role of G9a and the DNMTs in regulating gene silencing in MM, and support dual epigenetic inhibition as a promising therapeutic strategy.